1980
DOI: 10.1542/peds.65.2.364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neonatal Intensive Care on Neonatal Mortality in Chile

Abstract: Up to the year 1975, neonatal care in our unit consisted of: pediatricians and nurses without specialization in neonatology; equipment basically limited to incubators; and treatment of premature infants and neonates with respiratory problems reduced to: (1) temperature control, (2) prevention of infection, (3) careful feeding and fluid administration, (4) oxygen therapy based on clinical appearance of cyanosis, and (5) correction of acidosis with NaHCO3. See table in the PDF file … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on that experience, we make the following comments, hoping that they will add some insight to a controversial and complicated issue.The issues are not really new, but continue to be problematic for many infants. In 1980, Ventura-Junca et al 3 clearly showed the effectiveness of neonatal intensive care in reducing mortality in Chile, confirming for an emerging nation what was also described by the Office of Technology Assessment for the whole of the United States, namely that neonatal intensive care is effective in reducing infant mortality. Recently, we published a survival rate of 78% in 1,200 newborns treated with intensive respiratory care in one NICU in an emerging country.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Based on that experience, we make the following comments, hoping that they will add some insight to a controversial and complicated issue.The issues are not really new, but continue to be problematic for many infants. In 1980, Ventura-Junca et al 3 clearly showed the effectiveness of neonatal intensive care in reducing mortality in Chile, confirming for an emerging nation what was also described by the Office of Technology Assessment for the whole of the United States, namely that neonatal intensive care is effective in reducing infant mortality. Recently, we published a survival rate of 78% in 1,200 newborns treated with intensive respiratory care in one NICU in an emerging country.…”
mentioning
confidence: 61%
“…Many infants in NICUs in the developing world continue to have major problems with infection. 3,4 This is not to say that infections do not occur at somewhat alarming rates in NICUs in industrialized and more developed nations. However, the rates of infection are decreased by education and organization, and not necessarily by expensive measures.…”
mentioning
confidence: 99%